Société de l’aveu, cis-tème de l’aveu : repenser le consentement à la lumière des images intimes de personnes trans* dans les medias - Alexandre Baril (Glad!)
Despite feminist redefinitions of sexual consent that highlight its renewable, affirmative, retractable nature, legal consent to the public distribution of any type of image requires only a single, irrevocable instance of consent. I argue that it is problematic to consider consent to publicly distribute intimate nude images in the same way as consent to sharing other images. What if consent to the public distribution of intimate images were redefined according to feminist understandings of sexual consent? Using the example of trans* people and inspired by Foucault’s work on confessing, I argue that we live in a “confessing society” that leads us to believe that disclosing our deepest selves is liberating and a transphobic/cisgenderist “confessing cis-tem” that, together, push trans* people to show their naked bodies/souls to satisfy public curiosity. Adopting a feminist, transactivist approach and an auto-ethographic methodology based on my experience as a trans man who reluctantly undressed for media projects on my transition for which my consent cannot be retracted, I present two arguments. First, for some trans* people, certain aspects of the confessing cis-tem, including social and media pressures, should be considered factors that can bias consent. Second, I call for a redefinition of consent to the distribution of intimate images: whether consent is given in biased circumstances or not, it should be possible to withdraw it, as with sexual consent. If people can reconsider being intimate with just one other person, the same should be true of exposing their nudity to an audience.